2021
DOI: 10.1039/d1py00422k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and self-assembly of amphiphilic precision glycomacromolecules

Abstract: We present the synthesis of so called amphiphilic glycomacromolecules (APGs) by using solid-phase polymer synthesis. Based on tailor made building blocks, monosdisperse APGs with varying compositions are synthesized, introducing carbohydrate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…As building blocks, previously established TDS (triple‐bond diethylenetriamine coupled with succinic acid), [ 9 ] ADS (azide diethylenetriamine coupled succinic acid), HDM (hexamethylenediamine coupled with maleic acid) along with azido‐functionalized acetylated α ‐D‐Man, β ‐Gal, CATE (carboxylated aromatic thioether luminophore) and the commercially available functional TPE luminophores were used. [ 37–43 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As building blocks, previously established TDS (triple‐bond diethylenetriamine coupled with succinic acid), [ 9 ] ADS (azide diethylenetriamine coupled succinic acid), HDM (hexamethylenediamine coupled with maleic acid) along with azido‐functionalized acetylated α ‐D‐Man, β ‐Gal, CATE (carboxylated aromatic thioether luminophore) and the commercially available functional TPE luminophores were used. [ 37–43 ]…”
Section: Resultsmentioning
confidence: 99%
“…As building blocks, previously established TDS (triple-bond diethylenetriamine coupled with succinic acid), [9] ADS (azide diethylenetriamine coupled succinic acid), HDM (hexamethylenediamine coupled with maleic acid) along with azido-functionalized acetylated 𝛼-D-Man, 𝛽-Gal, CATE (carboxylated aromatic thioether luminophore) and the commercially available functional TPE luminophores were used. [37][38][39][40][41][42][43] In short, the synthesis started from an amine-functionalized preloaded glycine resin and employed the stepwise addition of building blocks, which carry a free carboxylic acid group for attachment onto the resin and a protected amine group. Coupling was promoted by using the activation reagent benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate to form the active ester derivative.…”
Section: Synthesis Of Aie-apgsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study from our own lab, Banger et al 134 demonstrated that fixing spherical architectures of glycomacromolecules by cross-linking can benefit the binding of bacteria. Using solid-phase polymer synthesis with tailor-made building blocks, a small library of monodisperse amphiphilic glycomacromolecules (APGs) was generated.…”
Section: Introductionmentioning
confidence: 99%